Situación pre y post-incendio, de un ecosistema del tipo forestal Roble-Hualo, región del Maule, Chile - Rosales-Rodríguez, Jorge Alejandro (Instituto Tecnológico de Costa Rica, 2017)
Forest fires are one of the major causes of ecosystem degradation in Chile, most recently the 2016-2017 forest fire season highlighted by the affected area, within this is a forest and scrub, of the Roble-Hualo forest type, considered as high conservation value, so the effect of the fire was studied, in both coverages, on the structure of the canopy by using hemispheric photographs, in addition the effect of the fire was quantified on chemical variables of the soil, diversity and abundance of vegetation, for which six plots of 14 x 14 m were established, three for cover. The results indicated a clear degradation of the structure of the canopy of the forest and scrub, increase in the potential radiation on the forest floor, reduction of the foliar area and coverage of the canopies on the ground, some chemical variables such as pH, organic matter, sum of bases and available potassium increased in the scrub soil, but not in the forest soil. Post-fire regeneration was scarce in both coverages, in addition there was a considerable loss of arboreal and shrubby diversity, thus affecting the composition of the vegetation, in the forest and in the scrub.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Dosel; Suelo; Incendios forestales; Vegetación; Conservación; Ecosistemas